Answer:
![p(x)=(x+2)(x^2+x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/2t5dsz9ldkkv19yjq6cmf1cual2tr03pyw.png)
![x=-2](https://img.qammunity.org/2023/formulas/mathematics/college/hgapxsmy5hypkh6t7zmgcc8cu0ivm02dxk.png)
![x=(-1 + √(3)\:i)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/pdl1kihg303nv7pt0nm7xffipe7bnrskn6.png)
![x=(-1- √(3)\:i)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/2ibo1brbghsdcre62smwfg89q3hiepnbg1.png)
Explanation:
Given polynomial:
![p(x)=x^3+3x^2+3x+2](https://img.qammunity.org/2023/formulas/mathematics/college/be82nfwbyq1w9ahdcvkwb50rc8p3il1k2z.png)
Rational Root Theorem
If P(x) is a polynomial with integer coefficients and if p/q is a root of P(x), then p is a factor of the constant term of P(x) and q is a factor of the leading coefficient of P(x).
Possible p-values
Factors of the constant term: ±1, ±2
Possible q-values
Factors of the leading coefficient: ±1
Therefore, all the possible values of p/q:
![\sf (p)/(q)=(\pm 1)/(\pm 1), (\pm 2)/(\pm 1)=\pm1,\pm2](https://img.qammunity.org/2023/formulas/mathematics/college/yrx85jolyh021158egmp2lskh3qm3whb14.png)
Substitute each possible rational root into the function:
![x=-1 \implies p(-1) =(-1)^3+3(-1)^2+3(-1)+2=1](https://img.qammunity.org/2023/formulas/mathematics/college/yogsahvnl5skeac9wtz3e0t5pt7g7tz4j6.png)
![x=1 \implies p(1) =(1)^3+3(1)^2+3(1)+2=9](https://img.qammunity.org/2023/formulas/mathematics/college/ws4wrk866j05rq9qnss77jffyc5je0ia4l.png)
![x=-2 \implies p(-2) =(-2)^3+3(-2)^2+3(-2)+2=0](https://img.qammunity.org/2023/formulas/mathematics/college/gg49sik89auzx18mj8gmrj8ew4pm540dru.png)
![x=2 \implies p(2) =(2)^3+3(2)^2+3(2)+2=28](https://img.qammunity.org/2023/formulas/mathematics/college/npuiogcxqfnjhl0bxmc3v7jn7jwtcidtqx.png)
Therefore, x = -2 is a root of the polynomial since f(-2) = 0.
Divide the polynomial by the root using synthetic division:
![\begin{array}c-2 & 1 & 3 & 3 & 2\\\cline{1-1} & \downarrow &-2&-2&-2\\ \cline{2-5} & 1&1&1&0\end{array}](https://img.qammunity.org/2023/formulas/mathematics/college/k79y7rey8i1zmjaqjr2wnz3wk5uno0wv1f.png)
The bottom row (except the last number) gives the coefficients of the quotient. Therefore, the quotient is:
![x^2+x+1](https://img.qammunity.org/2023/formulas/mathematics/college/7z03ksqolzpwnbpu07ezpph7m0dw43vx6x.png)
So the fully factored form of p(x) is:
![p(x)= (x+2)(x^2+x+1)](https://img.qammunity.org/2023/formulas/mathematics/college/wsm5pgsyt36v2oso4x9sxml010vbuf2uic.png)
![\boxed{\begin{minipage}{3.6 cm}\underline{Quadratic Formula}\\\\$x=(-b \pm √(b^2-4ac))/(2a)$\\\\when $ax^2+bx+c=0$ \\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/y4o8yi6a03inhmfcrws9qy06m74fwoktuh.png)
Therefore, the solutions to the quadratic factor are:
![\implies x=(-1 \pm √(1^2-4(1)(1)))/(2(1))](https://img.qammunity.org/2023/formulas/mathematics/high-school/26wfg8gk2a3k0fmzghmznkr87rxztnjtq2.png)
![\implies x=(-1 \pm √(-3))/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/spn3bg0sq7gf3p1hoin10c0rhmq8kr6gt4.png)
![\implies x=(-1 \pm √(3\cdot -1))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/e1v5nvw05zutwyke5k6477plmgzoz25q9f.png)
![\implies x=(-1 \pm √(3) √(-1))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/opsxagwquy7madnfuw1enfoc4mk4dtd0qa.png)
![\implies x=(-1 \pm √(3)\:i)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/3ustb7vuyrvglbk6594vs165tdxoj08otu.png)
The 3 solutions of p(x) are: